Metallothionein: A potential link in the regulation of zinc in nutritional immunity - Rahman, Mohammad Tariqur; Karim, Muhammad Manjurul (Humana Press, 2018)
Nutritional immunity describes mechanisms for withholding essential transition metals as well as directing the toxicity of these metals against infectious agents. Zinc is one of these transition elements that are essential for both humans and microbial pathogens. At the same time, Zn can be toxic both for man and microbes if its concentration is higher than the tolerance limit. Therefore a Bdelicate balance of Zn must be maintained to keep the immune cells surveilling while making the level of Zn either to starve or to intoxicate the pathogens. On the other hand, the invading pathogens will exploit the host Zn pool for its survival and replication. Apparently, different sets of protein in human and bacteria are involved to maintain their Zn need. Metallothionein (MT)—a group of low molecular weight proteins, is well known for its Zn-binding ability and is expected to play an important role in that Zn balance at the time of active infection. However, the differences in structural, functional, and molecular control of biosynthesis between human and bacterial MT might play an important role to determine the proper use of Zn and the winning side. The current review explains the possible involvement of human and bacterial MT at the time of infection to control and exploit Zn for their need.